2021
DOI: 10.3390/ijms22020963
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: A Key Piece in Asthmatic Inflammation

Abstract: Asthma is a chronic disease of the airways that has an important inflammatory component. Multiple cells are implicated in asthma pathogenesis (lymphocytes, eosinophils, mast cells, basophils, neutrophils), releasing a wide variety of cytokines. These cells can exert their inflammatory functions throughout extracellular vesicles (EVs), which are small vesicles released by donor cells into the extracellular microenvironment that can be taken up by recipient cells. Depending on their size, EVs can be classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 223 publications
0
14
0
Order By: Relevance
“…Studies have shown that exosomes are involved in many inflammatory processes, such as acute lung injury, inflammatory bowel disease, and asthma inflammation. ( Canas et al, 2021 ; Monsel et al, 2016 ; Zhang et al, 2019 ). We therefore hypothesized that exosomes play a role in the crosstalk between macrophages and BMSCs under inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exosomes are involved in many inflammatory processes, such as acute lung injury, inflammatory bowel disease, and asthma inflammation. ( Canas et al, 2021 ; Monsel et al, 2016 ; Zhang et al, 2019 ). We therefore hypothesized that exosomes play a role in the crosstalk between macrophages and BMSCs under inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that TSLP-activated DCs release OX40L expressing exosomes that drive CD4+ TH2 proliferation and differentiation [66]. Exosomes are involved in asthmatic inflammation which has been reviewed in depth by Cañas et al [67]. MicroRNAs seem to play a significant role in the asthmatic process, which was supported by findings that miRNA is differentially expressed in the sputum of asthma patients [68,69].…”
Section: Exosomes In Allergic Sensitization and Inflammationmentioning
confidence: 95%
“…The exosomes produced by T cells activate and degranulate mast cells and release cytokines, leading to tissue remodeling and airway hyper-responsiveness ( 99 ). Similarly, exosomes released by B lymphocytes transport specific molecules of antigen-presenting cells, enabling these exosomes to present the antigen to induce T-cell responses and release IL-5 and IL-13 cytokines ( 100 ).…”
Section: Exosomes In Immune Tolerance and Autoimmunitymentioning
confidence: 99%